Strategi Satgas PPKS dalam Memberikan Perlindungan Hak Korban Kekerasan Seksual di Lingkungan Perguruan Tinggi : Strategi Satgas PPKS - Febriandari, Yulia (UIR Law Review, 2023)
This research discusses the strategy of sexual violence task foece in carrying out its duties and authority to provide protection for the rights of victims of violece and the obstacles because there is a lot of sexual violece occuring in universities, therefore they are interested in conducting deeper research by examining several universities, the aimof the research is to determine the strategy of the sexual violence task force in carrying out its duties and authority in providing protection for the rights of victims of sexual violence in the tertiary environment and the obstacles they experience. The research method used in this research method leads to empirical juridical research, namely research carried out by examming primary data obtained in the field, namely based on the results of interviews that have been answered by sources and absevations.